P257 THE IMPORTANCE OF ADMINISTERING A PHYSICAL EXERCISE PROGRAM WITH A NUTRITIONAL INFORMATION SHEET TO PATIENTS SUFFERING FROM CONGESTIVE HEART FAILURE INCLUDED IN A FOLLOW–UP PROGRAM WITHIN A DEDICATED CLINIC. (18th May 2022) - De Masi De Luca, G; Stefanelli, S; Longo, S; Barba, F; Mauro, R; Marzo, S; Papadia, P; Accogli, M
Abstract: Background: With this work we wanted to draw attention on the importance of administering a physical exercise path sheet and nutritional information sheet to patients with congestive heart failure (HF) in a FUP path. Materials and methods 164 patients were included in the FUP course dedicated to the HF at the dedicated outpatient clinic of the "Card.G. Panico" hospital in Tricase (Lecce, IT) in collaboration with the "Cardiomed Center" in Maglie (Lecce, IT). During the evaluation of insertion in the FBD, patients were divided according to the risk of events: low, medium and high. To improve adherence, both the patient and his caregiver obtained adequate and detailed information about the importance of the project and its aims. Patients with greater clinical stability, at medium and low risk (102) were divided into two groups. The FUP path was ideal for both, but only in the first (58 Group A) had a sheet with a personalized physical exercise path (PEP) and a sheet with nutritional information (SNI), identifying it as a real additional pharmacological therapy. The aim of the work was to highlight how an education and invitation to carry out physical exercise and an adequate nutritional path can bring benefit by evaluating medium–short term parameters that are weight, Borg scale, BNP, clinical alerts. Results: The following differences were observed in the group of patients followed in the follow–up of Group A to whom the PEP and SNI sheets were administered compared to group B. – Alert in group A: 10 (7 diuretic therapy correction for OS, 1 access to the ER, 2 coomorbidity corrections) — Alert in group B: 18 (9 correction of diuretic therapy, 4 accesses to the ER, 1 hospitalization, 4 coomorbidity correction) P < 0.05 — BNP group A Δ –122 / group B Δ –188 P n.s. — Borg scale (0/10) Group A Δ + 1.9 / Group B Δ –0.2 P < 0.05 – Weight (kg) Group A –9% / Group B + 1% P < 0.05 Conclusions: Our experience in the clinic dedicated to heart failure has demonstrated the improtance and usefulness of administering a personalized physical exercise sheet to an adequate nutritional path, highlighting the improvement of various parameters such as weight, the perception of effort and the reduction of clinical alerts in the medium–short term.